Development of a computer-assisted learning courseware for anatomy and physiology of swallowing - Yee, Fun Chow; Rahayu Mustaffa Kamal,; Shobha Sharma,; Susheel Kaur Dhillon Joginder Singh,; Hua, Nong Ting (Penerbit Universiti Kebangsaan Malaysia, 2018)
Knowledge of normal anatomy and physiology of swallowing is fundamental in the identification of individuals with or at risk for swallowing disorders. Learning anatomy and physiology however, is not an easy task thus, computer-assisted learning (CAL) approaches have been incorporated into the learning of the topics to enhance understanding. Although evidence exists on the benefits of using CAL in education, more studies are necessary in the field of swallowing. While courseware for the learning of anatomy and physiology of swallowing exist, they are not comprehensive. Therefore, this study aimed to develop a comprehensive CAL courseware for anatomy and physiology of swallowing. The current study used a designed-based research following the ADDIE (analysis, design, development, implementation, and evaluation) model to create a multimedia courseware, incorporating the use of text, still images, animations, audio narrations, and presented on a simple graphical user interface. The courseware was evaluated by 27 undergraduate students in terms of its usefulness, ease of use, and users’ satisfaction. Results indicate that the participants were satisfied with the courseware and that they perceived the courseware as useful, easy to learn and easy to use. The study represents an initiative to investigate the use of CAL in the subject and to establish the basis for further work which includes assessment on the learning outcomes from the usage of the CAL courseware. It is hoped that the use of this courseware in teaching and learning of anatomy and physiology of swallowing can enhance students’ knowledge and understanding of the area efficiently and effectively.